2004
DOI: 10.4049/jimmunol.172.9.5765
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Anti-Plasmin Antibodies in the Antiphospholipid Syndrome That Inhibit Degradation of Fibrin

Abstract: The combined presence of anti-phospholipid Ab (aPL) and thrombosis is recognized as the antiphospholipid syndrome (APS). The aPL represent a heterogeneous group of Ab that recognize various phospholipids (PL), PL-binding plasma proteins, and/or PL-protein complexes. Recently, we found the presence of antithrombin Ab in some APS patients and that some of these anti-thrombin Ab could inhibit thrombin inactivation by antithrombin. Considering that thrombin is homologous to plasmin, which dissolves fibrin, we hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
95
1
4

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 39 publications
3
95
1
4
Order By: Relevance
“…9,12-14 Notably, high affinity monoclonal anti-plasmin antibodies isolated from patients with APS bind plasminogen, thrombin, factor X, and activated protein C with considerably lower affinity. 12,14 Typically, these autoantibodies seem to cross-react with epitopes within the catalytic domains of serine proteases and conformational epitopes in ␤2 glycoprotein 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,12-14 Notably, high affinity monoclonal anti-plasmin antibodies isolated from patients with APS bind plasminogen, thrombin, factor X, and activated protein C with considerably lower affinity. 12,14 Typically, these autoantibodies seem to cross-react with epitopes within the catalytic domains of serine proteases and conformational epitopes in ␤2 glycoprotein 1.…”
Section: Discussionmentioning
confidence: 99%
“…14 Briefly, 12 M plasmin was incubated with 6 mM TLCK in PBS (pH 7.4) for 100 minutes at 25°C. 14 Using this method, the proteolytic activity of plasmin is reportedly inhibited in excess of 99%.…”
Section: Elisamentioning
confidence: 99%
“…We previously reported that some Abs derived from APS patients bind to the homologous enzymatic domains of several serine proteases (SP) involved in coagulation, such as thrombin, activated PC, plasmin, tissue plasminogen activator, and FXa (10,12,14,15,17). Moreover, some of these autoantibodies are prothrombotic and interfere with different anticoagulation pathways and/or fibrinolytic process (10,12,14,15,17,32).…”
mentioning
confidence: 99%
“…Moreover, some of these autoantibodies are prothrombotic and interfere with different anticoagulation pathways and/or fibrinolytic process (10,12,14,15,17,32). FIXa also belongs to the SP family and its enzymatic domain is homologous to those of thrombin and FXa (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation